2013
DOI: 10.1016/j.nimb.2012.12.118
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the characterization of ion implanted hexagonal boron nitride

Abstract: The effect of ion implantation on hexagonal boron nitride (h-BN) is studied herein. We use boron as an ion of choice to introduce radiation damage into h-BN, at fluences ranging from 1 x 10 14 -1 x 10 16 ions/cm 2 and implantation energy ranges from 40 to 160 keV. The thermal dependence is also investigated by varying the annealing temperature from room temperature to 400 °C after implantation. Raman spectroscopy showed Raman active defects one of which is possibly related to the formation of cubic boron nitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
(15 reference statements)
1
10
1
Order By: Relevance
“…Hardness testing of the implanted BN samples was carried out using the FM-700 micro- Cubic BN with nanoscale particles tends to show the LO phonon modes [4,[7][8], shifted to lower energies, as we see here after implantation as broad peaks around 1300 cm -1 ; this peak indicates a phase change to cubic-BN, as reported in detail before [1][2][3][4][5].…”
Section: Micro-indentationsupporting
confidence: 69%
See 2 more Smart Citations
“…Hardness testing of the implanted BN samples was carried out using the FM-700 micro- Cubic BN with nanoscale particles tends to show the LO phonon modes [4,[7][8], shifted to lower energies, as we see here after implantation as broad peaks around 1300 cm -1 ; this peak indicates a phase change to cubic-BN, as reported in detail before [1][2][3][4][5].…”
Section: Micro-indentationsupporting
confidence: 69%
“…Cubic BN is synthesized in industrial quantities under pressure, but it has been shown that the implantation of light ions into h-BN can trigger a phase change to c-BN, which forms a thin layer of nanoparticles (9nm) within the implanted region. From Raman, X-ray and infrared analyses [1][2][3][4][5] there is an optimum ion fluence for He + , Li + , B + and N + which decreases as the ion mass increases. The creation of interstitial defects is thought to tip the structure from hexagonal layers to the tetrahedral cubic form.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Three different samples have been used in a previous work (12,13) including polycrystalline rods, polycrystalline sheets and single-crystal h-BN samples. *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Raman measurements under similar conditions of temperature and energy for different fluences have been reported in [37], [44]. The Raman lineshape and position for c-BN will vary depending of the size of the crystals being analysed.…”
Section: Haadf-stem and Hrtemmentioning
confidence: 73%